The relationship between background music and customers' emotion towards duration of stay in restaurants / Farhan Faat... [et al.] - Faat, Farhan; Shahuri, Shakuraitul Aine; Ismail, Natrah; Nik Mohd Nor, Nik Mohd Shahril; Nordin, Nakia (UiTM Cawangan Johor, 2019)
Food service in Malaysia has grown positively and to a certain extent is being labelled as 'sophisticated'. The atmosphere in restaurants such as the colours, scents, temperature and music have become some of the essential elements that influence customers' behaviour. Previous studies have shown that music genre, rhythm and tempo were able to arouse the emotion of customers, thus affecting the patrons' consumption and duration of stay. Therefore, this study aims at reporting the empirical investigation of background music, emotions and duration of customers' stay in cafés and restaurants. The findings of this study revealed the relationship of the background music managed to arouse the emotion of patrons which led to lengthening the duration of customers' stay and increasing their consumption. The positive response among the customers indicated that the use of music in restaurants plays an integral part. As such, it is important for restaurateurs to choose suitable music to create pleasant atmosphere as it influences customers' emotion.